2007
DOI: 10.1111/j.1442-2050.2007.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric morbidity among patients with cancer of the esophagus or the gastro-esophageal junction: a prospective, longitudinal evaluation

Abstract: Cancer of the esophagus is often diagnosed at a late stage and is related to severe morbidity and a low 5-year survival rate. Previous studies have reported low health-related quality of life and high suicide rates for these patients. The occurrence of psychiatric morbidity and thus the potential need for psychological support may vary over time after diagnosis. This has not been adequately studied in patients with newly diagnosed cancer of the esophagus or gastro-esophageal junction. The present study therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 23 publications
(92 reference statements)
4
42
1
4
Order By: Relevance
“…Prospective study showed that anxiety and depression were prevalent at diagnosis of cancer (Gil et al, 2012;Iwatani et al, 2013). Over 1/3 of patients newly diagnosed with esophageal cancer suffered from significant psychological symptoms, particularly anxiety (Bergguist et al, 2007;Dempster et al, 2012). Pain, fatigue, insomnia and mood disturbance are highly prevalent in patients, especially the elderly undergoing cancer therapy (Cheng et al, 2011;Stauder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Prospective study showed that anxiety and depression were prevalent at diagnosis of cancer (Gil et al, 2012;Iwatani et al, 2013). Over 1/3 of patients newly diagnosed with esophageal cancer suffered from significant psychological symptoms, particularly anxiety (Bergguist et al, 2007;Dempster et al, 2012). Pain, fatigue, insomnia and mood disturbance are highly prevalent in patients, especially the elderly undergoing cancer therapy (Cheng et al, 2011;Stauder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These concerns seem reasonable given the prevalence of anxiety or depression in people with cancer [8][9][10] and the correlation with disease stage in some [11][12][13] but not all studies. [14][15] However, the majority of patients with advanced cancer express clear preferences for honest prognostic disclosure. 16 Furthermore, people with advanced cancer who discussed preferences for endof-life care with their oncologists were more likely to receive less aggressive medical care and have improved quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Ainda assim, a prevalĂȘncia que encontramos foi superior aos 5% de alguns estudos que utilizaram critĂ©rios diagnĂłsticos estritos, como por exemplo, episĂłdio depressivo grave (major depression) 8,9 . É inferior, no entanto, a um trabalho recente no qual tambĂ©m se utilizou a HAD em 94 pacientes com cĂąncer de esĂŽfago, chegando-se a uma cifra de 42% para casos "provĂĄveis e possĂ­veis de depressĂŁo" 27 . Entretanto Ă© difĂ­cil realizarmos uma comparação jĂĄ que grande parte dos trabalhos avalia grupos especĂ­ficos de pacientes oncolĂłgicos.…”
Section: Discussionunclassified